2023
DOI: 10.1111/pim.13018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the long‐term and short‐term protection in mouse model of Leishmania major infection following vaccination with Live Iranian Lizard Leishmania mixed with chitin microparticles

Mina Noroozbeygi,
Nafiseh Keshavarzian,
Mostafa Haji Molla Hoseini
et al.

Abstract: Inducing long‐term immunity is the primary goal of vaccination. Leishmanisation using non‐pathogenic to human Leishmania spp. could be considered a reliable approach to immunising subjects against Leishmania infection. Here, we evaluated the long‐term immune responses (14 weeks) after immunisation with either live‐ or killed‐Iranian Lizard Leishmania (ILL) mixed with chitin microparticles (CMPs) against L. major infection in BALB/c mice. In total, nine groups of mice were included in the study. To evaluate sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Leishmania tarentolae has also been investigated as vaccines against human pathogenic Leishmania species ( Bandi et al, 2023 ). After Breton et al showed that intra-peritoneal administration of live L. tarentolae in BALB/c mice induces a Th1 pathway with significant protection against L. donovani infectious challenge ( Breton et al, 2005 ), non-engineered live L. tarentolae promastigotes were assayed as candidate vaccines adjuvanted with CpG oligonucleotides ( Keshavarzian et al, 2020 ), or chitin microparticles against L. major ( Haghdoust et al, 2022 ; Noroozbeygi et al, 2023 ). Others employed genetically modified strains of L. tarentolae , engineered for overexpression of antigens from human pathogenic Leishmanias ( Saljoughian et al, 2013 ; Topuz Ata et al, 2023 ) or antigens from the vector saliva ( Katebi et al, 2015 ; Lajevardi et al, 2022 ).…”
Section: Non-pathogenic Leishmania Tarentolae Para...mentioning
confidence: 99%
“…Leishmania tarentolae has also been investigated as vaccines against human pathogenic Leishmania species ( Bandi et al, 2023 ). After Breton et al showed that intra-peritoneal administration of live L. tarentolae in BALB/c mice induces a Th1 pathway with significant protection against L. donovani infectious challenge ( Breton et al, 2005 ), non-engineered live L. tarentolae promastigotes were assayed as candidate vaccines adjuvanted with CpG oligonucleotides ( Keshavarzian et al, 2020 ), or chitin microparticles against L. major ( Haghdoust et al, 2022 ; Noroozbeygi et al, 2023 ). Others employed genetically modified strains of L. tarentolae , engineered for overexpression of antigens from human pathogenic Leishmanias ( Saljoughian et al, 2013 ; Topuz Ata et al, 2023 ) or antigens from the vector saliva ( Katebi et al, 2015 ; Lajevardi et al, 2022 ).…”
Section: Non-pathogenic Leishmania Tarentolae Para...mentioning
confidence: 99%